Risk Factors of Post Endoscopic Retrograde Cholangiopancreatography Bacteremia - Kwak, Min-Sun (The Korean Society of Gastroenterology; the Korean Society of Gastrointestinal Endoscopy; the Korean Association for the Study of the Liver; the Korean Society of Neurogastroenterology and Motility; Korean Association for the Study of Intestinal Diseases; Korean College of Helicobacter and Upper Gastrointestinal Research; Korean Pancreatobiliary Association; Korean Society of Gastrointestinal Cancer, 2013)
BACKGROUND/AIMS: Bacteremia following endoscopic retrograde cholangiopancreatography (ERCP) is a severe complication, but the risk factors for this condition have not yet been clearly determined. Thus, the aim of this study was to investigate the risk factors of post-ERCP bacteremia. METHODS: Among patients who underwent ERCP from June 2006 to May 2009, we selected patients without any signs of infection prior to the ERCP procedures. Of these patients, we further selected those who experienced bacteremia after ERCP as well as two-fold age and sex-matched controls who did not experience bacteremia after ERCP procedures. We compared clinical, laboratory and technical aspects between these two groups. RESULTS: There were 70 patients (3.1%) who developed bacteremia after ERCP. In the multivariate analysis, a history of previous liver transplantation, an elevated serum alkaline phosphatase level and an endoscopic retrograde biliary drainage procedure were independent risk factors of post-ERCP bacteremia (p=0.006, p=0.001, and p=0.004, respectively). The microbiologic analysis revealed the presence of gram-negative organisms in 80% of the cases, and 11 patients had infections with bacteria expressing extended spectrum β-lactamases. Pseudomonas infection was significantly more common in patients who received liver transplantation as compared to patients without transplantation (p=0.014). CONCLUSIONS: A history of liver transplantation, elevated serum alkaline phosphatase levels and endoscopic retrograde biliary drainage procedure were independent risk factors of post-ERCP bacteremia and require additional attention in future studies.